CAMELS Dereceleme Sistemi ve Türk Ticari Bankacılık Sektöründe Başarısızlık Tahmini - (:unkn) unknown (My University, 2008)
CAMELS dereceleme sistemi (veya benzerleri) çeşitli ülkelerin bankacılık denetim otoriteleri tarafından yıllardır kullanılmaktadır. Bu çalışmada, mali oranlar kullanılarak temsili CAMELS dereceleri ve bileşenleri 1996-2000 yılları için hesaplanmıştır. CAMELS bileşenlerini oluşturan mali oranlar yardımıyla, 2001 yılında TMSF’ye devredilen bankalar diskriminant analizi, lojistik regresyon ve yapay sinir ağları modelleri kullanılarak tahmin edilmeye çalışılmıştır. Bulgular, bir bankanın TMSF’ye devrinin temsili CAMELS oranları kullanılarak tahmin edilebilmesinin mümkün olmadığını göstermiştir.

Banking supervisory agencies around the world have been utilizing CAMELS rating system (or variants) for many years. In this study, financial ratios were used to calculate representative CAMELS ratings and components for 1996 - 2000. The financial ratios, which were used to calculate the CAMELS components, were utilized to predict the transfer of commercial banks in 2001 to the SDIF by the use of discriminant analysis, logistic regression and neural network models. Findings of the study presented that it was not possible to predict the transfer of a bank to SDIF by the use of CAMELS ratios.
CAMELS Rating System and Forecasting the Financial Failure in the Turkish Commercial Banking Sector
Keywords: İktisat; İşletme